Trade-offs between growth and reproduction in wild Atlantic cod - Folkvord, Arild; Jørgensen, Christian; Korsbrekke, Knut; Nash, Richard David Marriott; Nilsen, Trygve; Skjæraasen, Jon Egil (Canadian Journal of Fisheries and Aquatic Sciences, 2014)
Animals partition and trade off their resources between competing needs such as growth, maintenance, and reproduction. Over a lifetime, allocation strategies should result in distinct trajectories for growth, survival, and reproduction, but such longitudinal individual data are difficult to reconstruct for wild animals and especially marine fish. We were able to reconstruct two of these trajectories in wild-caught Northeast Arctic cod (Gadus morhua) females: size-at-age was back-calculated from otolith growth increments, and recent spawning history was reconstructed from postovulatory follicles and present oocyte development. Our findings indicate distinct trade-offs between length growth and reproduction. Fish that sexually matured early had attained a larger size at age 3 than immatures, but onset of reproduction caused slower growth compared with immatures. We found that 6- and 7-year-old females skipping spawning grew significantly more in the year of missed spawning than females spawning for the second consecutive year. The latter tentatively supports the hypothesis that skipped spawning may occur as an adaptive life-history strategy, given the potential future fecundity gain with increased size. publishedVersion